High glucose‐induced Galectin‐1 in human podocytes implicates the involvement of Galectin‐1 in diabetic nephropathy. (14th October 2014) - Liu, Yinghong; Long, Luping; Yuan, Fang; Liu, Fuyou; Liu, Hong; Peng, Youming; Sun, Lin; Chen, Guochun
Abstract The diabetic milieu is believed to change the activity, or result in damage of podocytes—a key component of the glomerular filtration barrier and known to secrete matrix for glomerular basement membrane. This in turn contributes to diabetic nephropathy. However, how podocyte dysfunction is triggered in diabetic nephropathy remains ambiguous. Galectin‐1 belongs to Galectin family that bind to β‐galactoside residues of glycosylated proteins. We explored whether Galectin‐1 is dysregulated in diabetic nephropathy using three different techniques, namely real‐time polymerase chain reaction, western blotting, and immunofluorescent staining, to follow the expression of Galectin‐1 under high glucose levels in podocytes. High glucose consistently induced Galectin‐1 expression. Immunohistochemistry using a Galectin‐1‐specific antibody also showed elevated Galectin‐1 in renal tissues of diabetic patients with manifestation of nephropathy, indicating a correlation of Galectin‐1 overexpression with diabetic nephropathy. Upregulation of Galectin‐1 is associated with loss of podocin, which is important for the physiological function of podocytes and decreases in the renal tissues of diabetic nephropathy. Increased Galectin‐1 is a causal event for the high glucose‐induced loss of podocin, since silencing Galectin‐1 in podocytes increased podocin expression in the presence of 25 mM glucose. Thus expression of Galectin‐1 in diabetic nephropathy may serve as a marker and contribute to disease progression by interfering with podocin expression.